2020
DOI: 10.1016/j.jenvman.2020.111152
|View full text |Cite
|
Sign up to set email alerts
|

Governance networks around grasslands with contrasting management history

Abstract: Romanian grasslands have high nature value, being among the most important biodiversity hotspots at the European level. The European Union Common Agricultural Policy (CAP) contradicts the Biodiversity Strategy to 2020 objective by hindering coordinated grassland governance and collaboration among the involved actors. At the European level, few attempts have been made in creating conceptual strategies for implementing conservation measures in a multi-actor and multi-scale governance setting. Our paper focuses o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…The drought degree has increased or decreased in varying degrees from 2010 to 2018, mainly in South Asia and East Asia with wetter dry conditions had become drier and drier, changing to drier conditions, while severe dry conditions in certain areas had changed to wetter conditions. Other relevant studies have also confirmed the accuracy of this result (Ummenhofer et al, 2013;Manolache et al, 2020;Chandrasekara et al, 2021;Hina et al, 2021). In addition, the study of Manolache et al (2020) explored the obstacles of different grassland management measures and the uniqueness to be considered in the selection, which was of great significance to provide different grassland management schemes for grassland ecosystems with different drought degrees.…”
Section: Analysis Of Mann-kendall Test and Sen Trend Degrees In Asian Grassland Ecosystemsupporting
confidence: 60%
See 1 more Smart Citation
“…The drought degree has increased or decreased in varying degrees from 2010 to 2018, mainly in South Asia and East Asia with wetter dry conditions had become drier and drier, changing to drier conditions, while severe dry conditions in certain areas had changed to wetter conditions. Other relevant studies have also confirmed the accuracy of this result (Ummenhofer et al, 2013;Manolache et al, 2020;Chandrasekara et al, 2021;Hina et al, 2021). In addition, the study of Manolache et al (2020) explored the obstacles of different grassland management measures and the uniqueness to be considered in the selection, which was of great significance to provide different grassland management schemes for grassland ecosystems with different drought degrees.…”
Section: Analysis Of Mann-kendall Test and Sen Trend Degrees In Asian Grassland Ecosystemsupporting
confidence: 60%
“…Other relevant studies have also confirmed the accuracy of this result (Ummenhofer et al, 2013;Manolache et al, 2020;Chandrasekara et al, 2021;Hina et al, 2021). In addition, the study of Manolache et al (2020) explored the obstacles of different grassland management measures and the uniqueness to be considered in the selection, which was of great significance to provide different grassland management schemes for grassland ecosystems with different drought degrees. Combined with the results of this study, they could help decision-makers better formulate targeted prevention and control measures to deal with terrestrial ecological drought caused by climate change.…”
Section: Analysis Of Mann-kendall Test and Sen Trend Degrees In Asian Grassland Ecosystemsupporting
confidence: 60%
“…Hence, effective conservation also depends on the protection of biodiversity outside of PAs. To do so, the development of incentives for targeted management practices to retain high diversity of species and habitats should be prioritized [79], yet scientific research that can support management decision is largely lacking [80]. We conducted this study in Romania, a heterogeneous and species-rich country, comprising five biogeographical regions.…”
Section: Representation In Existing Protected Areas and Conservation Implicationsmentioning
confidence: 99%
“…The general aim of this paper is to understand the constellation of stakeholders involved in crane conservation in the CCZ. To achieve this, we performed a social network analysis, as it provides an ideal framework to analyze how management structures are formed and coordinated (Bodin et al, 2019; Manolache et al, 2020). We adopted the interview‐based participatory network‐mapping tool Net‐Map (Schiffer & Hauck, 2010).…”
Section: Introductionmentioning
confidence: 99%